2016
DOI: 10.1126/scitranslmed.aaf1164
|View full text |Cite
|
Sign up to set email alerts
|

Somatic PIK3CA mutations as a driver of sporadic venous malformations

Abstract: Venous malformations (VM) are vascular malformations characterized by enlarged and distorted blood vessel channels. VM grow over time and cause substantial morbidity because of disfigurement, bleeding, and pain, representing a clinical challenge in the absence of effective treatments (Nguyen et al., 2014; Uebelhoer et al., 2012). Somatic mutations may act as drivers of these lesions, as suggested by the identification of TEK mutations in a proportion of VM (Limaye et al., 2009). We report that activating PIK3C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
212
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(238 citation statements)
references
References 71 publications
12
212
0
5
Order By: Relevance
“…When expressed as mutant proteins in cultured ECs, recurrent mutations in TIE2 and PIK3CA resulted in the same cellular abnormalities, which were restored by the p110α-specific inhibitor [29]. In addition, the TIE2 and PIK3CA mutations resulted in the formation of VM lesions when mutant genes were expressed by transplanted ECs in mice [30,150], and in a genetic mouse model [31,32], respectively. These results indicate that the TIE2 receptor and the PIK3CA signal transducer participate in the same VM signalling pathway, opening new possibilities for evidence-based molecular therapies against VMs [29,31,32,150].…”
Section: Ang–tie System In Vascular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…When expressed as mutant proteins in cultured ECs, recurrent mutations in TIE2 and PIK3CA resulted in the same cellular abnormalities, which were restored by the p110α-specific inhibitor [29]. In addition, the TIE2 and PIK3CA mutations resulted in the formation of VM lesions when mutant genes were expressed by transplanted ECs in mice [30,150], and in a genetic mouse model [31,32], respectively. These results indicate that the TIE2 receptor and the PIK3CA signal transducer participate in the same VM signalling pathway, opening new possibilities for evidence-based molecular therapies against VMs [29,31,32,150].…”
Section: Ang–tie System In Vascular Diseasesmentioning
confidence: 99%
“…In addition, the TIE2 and PIK3CA mutations resulted in the formation of VM lesions when mutant genes were expressed by transplanted ECs in mice [30,150], and in a genetic mouse model [31,32], respectively. These results indicate that the TIE2 receptor and the PIK3CA signal transducer participate in the same VM signalling pathway, opening new possibilities for evidence-based molecular therapies against VMs [29,31,32,150]. Recent genetic analysis have revealed that allelic TIE2 double mutations are enriched in blue rubber bleb nevous syndrome (BRBN), characterized by multiple VM lesions [151].…”
Section: Ang–tie System In Vascular Diseasesmentioning
confidence: 99%
“…Two recent studies confirm the presence of PIK3CA mutations in VMs from human patients and support the notion that hyperactivation of the Tie2-PIK3CA-Akt pathway is responsible for lesion presentation [6, 7]. Castel et al used two mouse models expressing the H1047R PIK3CA mutant in either an endothelial compartment or sporadically in the body to show that aberrant PI3K signaling results in the development of VMs [6]. Similarly, Castillo et al expressed H1047R PIK3CA in the embryonic mesoderm in a mosaic fashion and in a heterozygous state, analogous to human disease context, and observed the development of subcutaneous VMs in different body sites [7].…”
mentioning
confidence: 62%
“…Tie2 mutations occur in about 50% of VM patients while PIK3CA mutations account for about 25% of patients with apparent mutual exclusivity [3], suggesting a functional redundancy between the two disease drivers. Two recent studies confirm the presence of PIK3CA mutations in VMs from human patients and support the notion that hyperactivation of the Tie2-PIK3CA-Akt pathway is responsible for lesion presentation [6, 7]. Castel et al used two mouse models expressing the H1047R PIK3CA mutant in either an endothelial compartment or sporadically in the body to show that aberrant PI3K signaling results in the development of VMs [6].…”
mentioning
confidence: 85%
See 1 more Smart Citation